'Clinobarylite'–barylite: order-disorder relationships and nomenclature. (2nd January 2018) - Merlino, Stefano; Biagioni, Cristian; Bonaccorsi, Elena; Chukanov, Nikita V.; Pekov, Igor V.; Krivovichev, Sergey V.; Yakovenchuk, Viktor N.; Armbruster, Thomas
Abstract: 'Clinobarylite', BaBe2 Si2 O7, was defined as a monoclinic dimorph of orthorhombic barylite. Subsequently, its crystal structure was also proved to be orthorhombic, differing from barylite in terms of the space group symmetry, Pmn 21 instead of Pmnb, and in unit-cell dimensions. Through the order-disorder (OD) theory, the polytypic relationships between 'clinobarylite' and barylite are described. 'Clinobarylite' corresponds to the MDO1 polytype, with unit-cell parameters a = 11.650, b = 4.922, c = 4.674 Å, space group Pmn 21 ; barylite corresponds to the MDO2 polytype, with a = 11.67, b = 9.82, c = 4.69 Å, space group Pmnb . The re-examination of the holotype specimen of 'clinobarylite' confirmed its orthorhombic symmetry. Its crystal structure has been refined starting from the atomic coordinates calculated for the MDO1 polytype and the refinement converged to R1 = 0.0144 for 929 observed reflections [Fo > 4σFo ]. Owing to their polytypic relationships, 'clinobarylite' and barylite should be conveniently indicated as barylite-1 O and barylite-2 O, respectively; the name 'clinobarylite' should be discontinued. This new nomenclature of the barylite polytypes has been approved by the Commission on New Minerals, Nomenclature and Classification of the International Mineralogical Association (IMA 13-E).